A Fossil Wood of Dipterocarpaceae from Pliocene Deposit in the West Region of Java Island, Indonesia - YANCE I. MANDANG; NORIKO KAGEMORI (Society for Indonesian Biodiversity, 2004)
Fossil woods in Java Island have been excavated and sold for outdoor ornaments or indoor decoration purposes since 30years ago. These fossils are in danger of being drained out without known identities, composition and history. This studywas aimed to find out the botanical identity and geographical aspect of a newly recovered silicified fossil wood from Bantenarea in the west region of Java Island. The fossil trunk 28 m in length and 105 cm in diameter was buried in a tuffaceoussandstone layer. The age of the stratum was thought to be Lower Pliocene. A small sample was cut from the outer part ofthe log and then ground to obtain thin section for anatomical observation. The main anatomical features of the fossil woodare as follows: wood diffuse porous; vessel almost exclusively solitary, vascicentric tracheid present; axial intercellular canalpresent, distributed in long tangential rows; fibers with distinctly bordered pit. These features show affinities of the fossilwood to the extant wood Dryobalanops of the family Dipterocarpaceae, regardless of the fact that this genus is no longer exists living in the natural forest of the present day Java Island.ïƒ£ 2004 Jurusan Biologi FMIPA UNS SurakartaKeywords: fossil wood, Dipterocarpaceae, Dryobalanoxylon, Pliocene, Java Island